THE MORAL VALUES IN “CHICKEN RUN” MOVIE - Bejo Sutrisno; Rizha Wijayaningdyah (Journal of English Language and Literature (JELL), 2018)
This thesis covers an analysis of movie. Moral value is one of the main aspects that emerges in the movie. The moral value in the movie makes an example in human’s life in reality. The importance of moral values in our lives is how to learn the life’s experience and the life will go on. Each person must have moral values respectively and should not give up if he or she gets a variety of obstacles and barriers in life. Everybody must still strive in a positive way in order to pursue their dreams and can become a reality and help each other in achieving dreams. The writer analyzed this movie in moral values by using qualitative research. This thesis describes about moral values which are found in this movie and about the effort of main characters to reach dream. Based on the analysis, the writer hopes everyone should still try to reach the dream. To elaborate the findings, the writer describes formative analysis by capturing the dialogue using detailed data. Other findings related to the study are stated